2014
DOI: 10.1002/pmic.201300084
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of kidney repair by human mesenchymal stromal cells after ischemia: A comprehensive view using label‐free MSE

Abstract: Acute kidney injury (AKI) is one of the more frequent and lethal pathological conditions seen in intensive care units. Currently available treatments are not totally effective but stem cell-based therapies are emerging as promising alternatives, especially the use of mesenchymal stromal cells (MSC), although the signaling pathways involved in their beneficial actions are not fully understood. The objective of this study was to identify signaling networks and key proteins involved in the repair of ischemia by M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 72 publications
(85 reference statements)
1
6
0
Order By: Relevance
“…transcription and translation regulation, cytoskeleton reorganization and protein folding. Some of these processes were also modulated in renal cells by the paracrine actions of BM-MSCs [41], supporting the importance of EVs secretion in the interaction between MSCs and renal cells. Interestingly, EV CTR and EV HPX also have specific signatures by modulating exclusive groups of proteins.…”
Section: Discussionmentioning
confidence: 62%
“…transcription and translation regulation, cytoskeleton reorganization and protein folding. Some of these processes were also modulated in renal cells by the paracrine actions of BM-MSCs [41], supporting the importance of EVs secretion in the interaction between MSCs and renal cells. Interestingly, EV CTR and EV HPX also have specific signatures by modulating exclusive groups of proteins.…”
Section: Discussionmentioning
confidence: 62%
“…These processes have been involved in the regulation of energy metabolism of damaged tubular epithelial cells by MSC treatment. 37 Moreover, AKI damage was associated with the upregulation of genes involved in inflammation, ECM-receptor interaction, The relative expression (RQ) of miRNAs in EV-Dsh was defined as FC evaluated as 2 2DDCt with respect to the reference sample (EV-CTRL) as described in Concise Methods (n=4 in each group; P,0.05).…”
Section: Discussionmentioning
confidence: 99%
“…The levels of mRNA after MTB infection did not correlate with the proteins level. A similar result demonstrated that when the most induced proteins in human mesenchymal stromal cells (HMSCs) were assayed by qPCR, the results do not match the results detected by MS [23]. This is a limitation of the current study.…”
Section: Discussionmentioning
confidence: 61%